Turbulence-driven magnetic reconnection and the magnetic correlation length: observations from magnetospheric multiscale in Earth's magnetosheath - Stawarz,J; Eastwood,J; Phan,T; Gingell,I; Pyakurel,P; Shay,M; Robertson,S; Russell,C; Le,Contel O (Physics of Plasmas, 2022)
Turbulent plasmas generate a multitude of thin current structures that can be sites for magnetic reconnection. The Magnetospheric Multiscale (MMS) mission has recently enabled the detailed examination of such turbulent current structures in Earth's magnetosheath and revealed that a novel type of reconnection, known as electron-only reconnection, can occur. In electron-only reconnection, ions do not have enough space to couple to the newly reconnected magnetic fields, suppressing ion jet formation and resulting in thinner sub-proton-scale current structures with faster super-Alfvénic electron jets. In this study, MMS observations are used to examine how the magnetic correlation length (λC) of the turbulence, which characterizes the size of the large-scale magnetic structures and constrains the length of the current sheets formed, influences the nature of turbulence-driven reconnection. We systematically identify 256 reconnection events across 60 intervals of magnetosheath turbulence. Most events do not appear to have ion jets; however, 18 events are identified with ion jets that are at least partially coupled to the reconnected magnetic field. The current sheet thickness and electron jet speed have a weak anti-correlation, with faster electron jets at thinner current sheets. When 20 ion inertial lengths, as is typical near the sub-solar magnetosheath, a tendency for thinner current sheets and potentially faster electron jets is present. The results are consistent with electron-only reconnection being more prevalent for turbulent plasmas with relatively short λC and may be relevant to the nonlinear dynamics and energy dissipation in turbulent plasmas.